Pengaruh Pemberian Daun Kelor Terhadap Peningkatan Hemoglobin Pada Ibu Nifas di RSIA Sitti Khadijah 1 Makassar - Hasriantirisna, Hasriantirisna; Nanda, Kiki Riskianti; Wulandari, Ikrawanty Ayu; Wahyuni, Sri (JURNAL KESEHATAN DELIMA PELAMONIA, 2024)
The Effect of Giving Moringa Leaves on Increasing Hemoglobin in Postpartum Women at RSIA Sitti Khadijah 1 Makassar in 2024 Anemia during the postpartum period can occur in mothers, where after giving birth the hemoglobin level is less than normal, and this condition can cause iron loss and can affect the lactation process and can result in the uterus not contracting because the blood does not provide enough oxygen to the uterus. . Post partum anemia is defined as if the Hb level is <11 g/dL at 8 weeks postpartum. The most common causes of postpartum anemia are inadequate Fe requirements during pregnancy and complications during childbirth. Moringa leaves (Moringa oleifera) have been proven to have a higher Fe content compared to other green vegetables at 28.29 mg, so they can be used as an alternative for treating anemia. Research objective: To determine the effect of giving Moringa leaves on increasing hemoglobin in postpartum women at RSIA Sitti Khadijah 1 Makassar in 2024. The method used in this research is a type of experimental research with a quasi-experimental design. The sampling technique used was purposive sampling technique, with a population of all postpartum mothers, and a sample of 30, selected using certain criteria which included an intervention group and a control group. Research results: Shows the influence of Moringa leaves on increasing hemoglobin in postpartum women with a p value (0.000). Conclusion: There is an effect of giving Moringa leaves on increasing hemoglobin in postpartum women Keywords: Moringa leaves, postpartum mothers, hemoglobinparagraph